RELASI ULAMA DAN PENGUASA MASA KOLONIALISME - Agung Perdana Kusuma (JURNAL INDO-ISLAMIKA, 2018)
In the 18th century, although the Dutch Company controlled most of the archipelago, the Netherlands also experienced a decline in trade. This was due to the large number of corrupt employees and the fall in the price of spices which eventually created the VOC. Under the rule of H.W. Daendels, the colonial government began to change the way of exploitation from the old conservative way which focused on trade through the VOC to exploitation managed by the government and the private sector. Ulama also strengthen their ties with the general public through judicial management, and compensation, and waqaf assets, and by leading congregational prayers and various ceremonies for celebrating birth, marriage and death. Their links with a large number of artisans, workers (workers), and the merchant elite were very influential.